Prevalence of Cardiovascular Risk Factors in a Sample from the Portuguese Population – an Analysis of e_COR Study - Alves, Catarina (2015)
Purpose: The identification and control of risk factors (RF) is a crucial measure to be able to act appropriately and reduce the risk of cardiovascular disease (CVD). e_COR is a national study that will be performed in the 5 Portuguese sub-regions. This study aims to contribute to produce scientific evidence for decision in public health, in particular to better define strategies in the area of cardiovascular prevention. The aim of the present report was to estimate the prevalence of major CVD risk factors and to evaluate the perception, treatment and control of diabetes, hypercholesterolemia, hypertriglyceridemia, and hypertension, using the data collected in three sub-regions (Norte, Centro and Lisboa regions).